First evidence of glyphosate and aminomethylphosphonic acid (AMPA) in the respirable dust (PM10) emitted from unpaved rural roads of Argentina - Ramirez Haberkon, Nancy; Aparicio, Virginia Carolina; Mendez, Mariano (Elsevier, 2021)
The aim of this work was to compare the concentration of glyphosate and AMPA in the PM10 and the actual PM10 emission from agricultural soils and unpaved roads, located inside and outside farm fields. To determine the actual PM10 emission by wind erosion, the actual wind erosion was estimated using the Wind Erosion Equation, and the PM10 emission efficiency was measured with the Easy Dust Generator. PM10 was collected in an electrostatic precipitator coupled to the Easy Dust Generator. Actual PM10 emission was 11.5 g ha⁻¹ year⁻¹ in agricultural soils and 4711.4 g ha⁻¹ year⁻¹ in unpaved roads. The high value of actual PM10 emission in unpaved roads was due to their high actual wind erosion and the high PM10 emission efficiency, while the low value in agricultural soils was due to their low actual wind erosion. Content of glyphosate in the PM10 ranged from 59 to 359 ug kg⁻¹ in agricultural soils, from 382 to 454 ug kg⁻¹ in unpaved roads inside farm fields, and from 39 to 639 ug kg⁻¹ in unpaved roads outside farm fields. Content of AMPA in the PM10 ranged from 387 to 7228 ug kg⁻¹ in agricultural soils, from 900 to 4138 ug kg⁻¹ in unpaved roads inside farm fields, and 98 to 500 ug kg⁻¹ in unpaved roads outside farm fields. AMPA concentration in PM10 was higher than that of glyphosate due to the longer persistence of AMPA than glyphosate. Glyphosate and AMPA concentrations in PM10 were higher than in soil, which is an additional risk that should be considered when the effect of PM10 emitted by agricultural soils and unpaved roads on human health are evaluated. Our results show that the amount and chemical composition of PM10 emitted by wind erosion from unpaved roads should be studied in other regions.